What drives taxi drivers? A field experiment on fraud in a market for credence goods - Loukas Balafoutas; Adrian Beck; Rudolf Kerschbamer; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2011)
Credence goods are characterized by informational asymmetries between sellers and consumers that invite fraudulent behavior by sellers. This paper presents the results of a natural field experiment on taxi rides in Athens, Greece, set up to measure different types of fraud and to examine the influence of passengers' presumed information and income on the extent of fraud. Results reveal that taxi drivers cheat passengers in systematic ways: Passengers with inferior information about optimal routes are taken on longer detours while asymmetric information on the local tariff system leads to manipulated bills. Higher income seems to lead to more fraud.
Keywords: C93; D82; 330; credence goods; expert services; natural field experiment; taxi rides; fraud; asymmetric information; Taxigewerbe; Betrug; Vertrauensgüter; Asymmetrische Information; Feldforschung; Athen